1981
DOI: 10.1111/j.1365-2125.1981.tb01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the frequency of daily dosage influence compliance with digoxin therapy?

Abstract: 1 The influence of daily dosage frequency on drug compliance has been studied in 80 outpatients for whom maintenance digoxin 0.25 mg daily had been prescribed. 2 Each patient took one tablet (0.25 mg) daily, two tablets (0.125 mg) daily and four tablets (0.0625 mg) daily in randomised order for 2 month periods. 3 Compliance was assessed by tablet counting and by serial measurement of the plasma digoxin concentration.4 Of the 67 patients (100%) who could have completed the study, 19 (28.4%) were withdrawn for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In view of this, it is perhaps surprising to find such a large number of patients who were grossly non-compliant, that is who had discontinued their treatment or took it only occasionally (19 patients or 30.2%). However, in a previous study of the influence of daily dose frequency on compliance with digoxin treatment, we also found that about 30% of patients were grossly unreliable, making measurements of the effects of different tablet numbers in them impossible (Taggart et al, 1981). One might have expected that a symptomatic illness such as obstructive airways disease would encourage compliance, but so many patients were receiving theophylline in amounts which produced plasma levels below 10 jig/ml or even below 5 ug/ml that it seems unlikely that failure to take the drug would result in symptomatic deterioration.…”
Section: Discussionmentioning
confidence: 81%
“…In view of this, it is perhaps surprising to find such a large number of patients who were grossly non-compliant, that is who had discontinued their treatment or took it only occasionally (19 patients or 30.2%). However, in a previous study of the influence of daily dose frequency on compliance with digoxin treatment, we also found that about 30% of patients were grossly unreliable, making measurements of the effects of different tablet numbers in them impossible (Taggart et al, 1981). One might have expected that a symptomatic illness such as obstructive airways disease would encourage compliance, but so many patients were receiving theophylline in amounts which produced plasma levels below 10 jig/ml or even below 5 ug/ml that it seems unlikely that failure to take the drug would result in symptomatic deterioration.…”
Section: Discussionmentioning
confidence: 81%
“…for such studies and accurate methods are needed. However, he also stressed that clinically important endpoints should be used, citing a study by Taggart et al (1981) which concluded that compliance with digoxin prescribed as a four times a day regimen was worse than with a once daily or twice daily regimen, but that the slightly lower digoxin levels on the four times a day regimen were unlikely to be of clinical importance.…”
Section: Horses For Coursesmentioning
confidence: 99%
“…Dosage frequently does not appear to have a major influence on the grossly noncompliant patient. 15 Other Considerations of Risk DISEASES The provider may want to factor the patient's diseased state into the process of establishing whether a patient is at risk of noncompliance. There are, of course, many disease states that pose a special risk to the elderly patient; several are mentioned here.…”
Section: Noncompliance In the Elderlymentioning
confidence: 99%